Perspectives of Social Exclusion and Structural Injustice among Students with Disabilities in Higher Education Level - Shanita Septias Anaway; Erinna Destanya Putri (International Disability Innovation Journal, 2026)
This study explores the experiences of social exclusion and structural injustice among students with disabilities in higher education. It aims to examine how systemic barriers, institutional practices, and social attitudes contribute to unequal academic experiences for students with disabilities. Despite increasing discourse on inclusive education, many higher education institutions continue to fall short in providing equitable access and support. This research employs a qualitative approach, utilizing questionnaires and in-depth responses from students with disabilities across various academic backgrounds. The data were analyzed using thematic analysis to identify recurring patterns related to exclusion, accessibility, and institutional support. The study focuses on key aspects such as physical accessibility, learning accommodations, social interaction, and policy implementation within the university setting. The findings reveal that students with disabilities frequently encounter multiple forms of exclusion, both visible and invisible. These include inadequate campus infrastructure, limited access to learning materials, lack of inclusive teaching practices, and persistent social stigma from peers and the academic community. Furthermore, structural injustice is reflected in the absence of consistent institutional policies and insufficient awareness among stakeholders, which often places the burden of adaptation on the students themselves. This study highlights the urgent need for higher education institutions to move beyond symbolic inclusion toward substantive equity. Strengthening inclusive policies, improving accessibility, and fostering disability awareness are essential steps in addressing systemic inequalities. By centering the voices and lived experiences of students with disabilities, this research contributes to a deeper understanding of the challenges they face and offers insights for developing more inclusive and just educational environments.